Assessment and characterization of the bacterial community structure in advanced activated sludge systems. (June 2019) - Cinà, Paolo; Bacci, Giovanni; Arancio, Walter; Gallo, Giuseppe; Fani, Renato; Puglia, Anna Maria; Di Trapani, Daniele; Mannina, Giorgio
Highlights: The bacterial community structures of five compartments were analyzed. Phylogenetic correlations based on the 16S rDNA sequence were carried out. Core community of bacteria can play a rheostatic role in bacterial structure. Biofilm communities possessed the greatest diversity. Abstract: The present study is aimed to assess and characterize the structure of bacterial community in advanced activated sludge systems. In particular, activated sludge samples were collected from an Integrated Fixed-film Activated Sludge – Membrane Bioreactor pilot plant under a University of Cape Town configuration with in-series anaerobic (Noair)/anoxic (Anox)/aerobic (Oxy) reactors – and further analyzed. The achieved results – based on Next Generation Sequencing (NGS) of 16S rDNA amplicons – revealed that the bacterial biofilm (bf) communities on plastic carriers of Oxy and Anox reactors had a greater diversity compared to suspended (sp) bacterial flocs of Oxy, Anox and Noair. Indeed, the Shannon diversity indices of both biofilm communities were higher than those of suspended growth samples (Oxy-bf = 4.1 and Anox-bf = 4.2 vs . Oxy-sp = 3.4, Anox-sp = 3.5 and Noair-sp = 3.4). The most striking differences have been reported in Rhodobacteraceae being more abundant in biofilm specimens than in suspended biomass samples. The vast majority of the identified bacteria differs from those obtained by culture dependent method, thus suggesting that NGS-based method is really suitable to analyze the bacterial community composition, even in advanced systems for wastewater treatment.